Handbook of water analysis - Nolley, Leo M. L. (CRC Press, 2007)
By organizing data into more than 300 tables, graphs, and charts, and supplementing the text with equations and illustrations, the editor distills a wealth of knowledge into a single accessible reference. Contributions from notable international scientists cover sampling methods, the treatment of data, and analyses of specific compounds, their assessment, and their toxicological, chemical, and environmental properties. The book summarizes problems with radionucleotides in the environment, presents techniques for measuring isotopes in water, explains analytical methods for detecting sulfur compounds, and provides practical guidelines and protocols for identifying the chemistry, occurrence, and significance of surfactants in water. It describes traditional distillation and gas-chromatography, including extraction and derivation steps, and the use of ion chromatography and capillary electrophoresis. It also highlights new methods for separating organic nitrogen compounds and discusses techniques for identifying metals, silicon, and asbestos in water samples.